Jigsaw Type Cooperative Learning Model Assisted by Flashcard Media in Social Science Learning - Briliyanti, Amalia Rahmah; Setiawan, Deni (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Lack of innovation in the application of learning models also contributes to the lack of active involvement of students in the learning process. This study aims to analyze the effectiveness of the application of the Jigsaw cooperative learning model assisted by Flashcard media in improving student learning outcomes in science subjects. This study is an experimental study with a one-group pretest-posttest design. The subjects used in this study were 23 students of class IV-A as the experimental class, and the control class used 24 students of class IV-B. Data collection techniques include observation, interviews, documentation, and tests. The research instruments used were learning activity observation sheets and learning outcome test questions. Data were analyzed using the N-Gain test to see the increase in student learning outcomes before and after treatment. The results showed a significant increase in student learning outcomes after the application of the learning model, with the category of improvement at a moderate level. This study concludes that the Jigsaw learning model assisted by Flashcard is efficacious in improving student learning outcomes in science subjects. This study provides implications that teachers need to consider the use of collaborative learning models and visually appealing media to support the achievement of learning objectives.